The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/mat.0000000000001697
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ventilator Settings With Mortality in Pediatric Patients Treated With Extracorporeal Life Support for Respiratory Failure

Abstract: Extracorporeal life support (ECLS) is a treatment for acute respiratory failure that can provide extracorporeal gas exchange, allowing lung rest. However, while most patients remain mechanically ventilated during ECLS, there is a paucity of evidence to guide the choice of ventilator settings. We studied the associations between ventilator settings 24 hours after ECLS initiation and mortality in pediatric patients using a retrospective analysis of data from the Extracorporeal Life Support Organization Registry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This study confirms other findings that ventilator F i O 2 is a potentially modifiable risk factor for poor outcomes in children on ECMO. 17,18 In recent years there has been much discussion and debate about awake and mobile ECMO. Kohne et al provided a foundation in this area by describing the current practice of tracheostomy in children on ECMO for respiratory indications.…”
Section: Resultsmentioning
confidence: 99%
“…This study confirms other findings that ventilator F i O 2 is a potentially modifiable risk factor for poor outcomes in children on ECMO. 17,18 In recent years there has been much discussion and debate about awake and mobile ECMO. Kohne et al provided a foundation in this area by describing the current practice of tracheostomy in children on ECMO for respiratory indications.…”
Section: Resultsmentioning
confidence: 99%
“…However, optimal lung-protective MV, in terms of mode and ventilator settings during ECMO, remains unproven. In a multisite, retrospective observational study of 204 children supported on venovenous ECMO for acute respiratory failure, patients with a Fio 2 requirement higher than 50% at day 3 of ECMO had a significantly higher death rate (46% vs 22%; p = 0.001) than those with Fio 2 equal or less than 50% (8), and these findings were duplicated in the ELSO Registry (9,10). No significant association between ventilatory settings such as PEEP, peak pressure, driving pressure, plateau pressure, and outcomes were found.…”
Section: Policy Statement 822 Centers Providingmentioning
confidence: 96%
“…T he 2015 Pediatric Acute Lung Injury Consensus Conference (PALICC) international recommendations on pediatric acute respiratory distress syndrome (PARDS) published 11 recommendations regarding the role of extracorporeal membrane oxygenation (ECMO) support in PARDS (1). Since 2015, there have been advances in ECMO research in adults with acute respiratory distress syndrome (ARDS) (2)(3)(4)(5)(6), devices and cannulas (7), management (8)(9)(10), and expanding indications, most notably COVID-19 (11)(12)(13).…”
mentioning
confidence: 99%
“…Currently, the correct management of the native lung during ECMO is still a matter of debate both in neonates and children. [9][10][11] Both Friedman ML et al 11 and Blauvelt DG et al 10 showed that the maintenance of high ventilator settings during ECMO (e.g. FiO 2 >60% and a PEEP >10 cmH 2 O) was associated with higher odds of mortality.…”
Section: Matteo DI Nardomentioning
confidence: 99%